2016
DOI: 10.1111/trf.13896
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of platelet senescence and platelet extracellular vesicles

Abstract: During in vitro senescence, PLTs degrade large RNA species. Concomitantly, they up-regulate a distinct set of known small RNA species involved in atherosclerosis, inflammation, and neurodegeneration. PL-EVs enrich miRNA species, likely supporting the role of PLTs and PL-EVs in vascular homeostasis and as carriers of neurodegenerative disease-related miRNA cargo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 111 publications
(151 reference statements)
1
32
0
Order By: Relevance
“…However, there are a few biological mechanisms that can endorse our finding. miR‐144‐3p has enriched expression and in the brain, as well as in normal and malignant hematopoietic cells and tissues . Many studies have suggested that miR‐144‐3p was involved in the response to stress, ageing diseases and mood stabilizer treatment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are a few biological mechanisms that can endorse our finding. miR‐144‐3p has enriched expression and in the brain, as well as in normal and malignant hematopoietic cells and tissues . Many studies have suggested that miR‐144‐3p was involved in the response to stress, ageing diseases and mood stabilizer treatment .…”
Section: Discussionmentioning
confidence: 99%
“…miR-144-3p has enriched expression and in the brain, as well as in normal and malignant hematopoietic cells and tissues. 44 Many studies have suggested that miR-144-3p was involved in the response to stress, ageing diseases and mood stabilizer treatment. 19,45,46 In addition, miR-144-3p can regulate ataxin 1 (ATXN1) mRNA expression in human cells, and a search of the Genetic Association Database shows that ATXN1 is associated F I G U R E 6 Correlation between miRNAs and their target mRNAs expression in the NAc tissue.…”
Section: Discussionmentioning
confidence: 99%
“…miR-144-3p has extensive expression nature which is enriched in human brain, additionally, also enriched in malignant hematopoietic and normal cells and tissues. 69 miR-144-3p is very conserved and has various envisaged targets in both mice and humans. Numerous investigations have revealed that miR-144-3p was implicated against response to stress, aging diseases, and mood stabilizer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is a key regulator in macrophage apoptosis, cardiac hypertrophy, atherosclerosis, and heart failure [18][19][20]. Platelet extracellular vesicles exhibit upregulated miR-142-5p, which is involved in vascular and metabolic disease [21]. miR-142 is suppressed in a hypertrophic heart model and human cardiomyopathic hearts [22].…”
Section: Discussionmentioning
confidence: 99%